2021
DOI: 10.1007/s12571-021-01189-1
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity during the COVID-19 pandemic: evidence from a survey of low-income Americans

Abstract: The COVID-19 pandemic significantly increased food insecurity despite emergency legislation that put more resources into food assistance programs, increased unemployment benefits, and provided stimulus payments. We conducted a survey in the US on food insecurity among low-income Americans during the early months of the pandemic. While we cannot estimate causal effects, we are able to show important associations between food insecurity and nutritional and economic assistance that highlight the need to ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 20 publications
3
47
0
Order By: Relevance
“…Similar declines in SNAP participation among vulnerable households in the months following the onset of the pandemic have been observed by others [ 30 , 42 ]. During the pandemic, initial SNAP policies that counted additional sources of benefits (e.g., unemployment insurance) towards household income may have made some households with children ineligible.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar declines in SNAP participation among vulnerable households in the months following the onset of the pandemic have been observed by others [ 30 , 42 ]. During the pandemic, initial SNAP policies that counted additional sources of benefits (e.g., unemployment insurance) towards household income may have made some households with children ineligible.…”
Section: Discussionsupporting
confidence: 85%
“…However, numerous barriers prevent some individuals from accessing these programs, including lack of information about the programs, difficulty applying, perception of stigma, and criteria restrictions [ 26 , 27 , 28 ]. While previous research has shown that participation in federal food and nutrition assistance programs increases during periods of economic hardship [ 29 ], pandemic-related barriers may have hampered program participation by some groups [ 30 , 31 ]. The use of food banks and pantries also increases in response to unmet food needs, as was evidenced by the long lines outside these facilities nationwide during the pandemic [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some mentioned the public charge rule as an impediment to SNAP enrollment, adding empirical evidence to support concerns about the rule's chilling effect on public assistance during the COVID-19 pandemic [26]. During the pandemic, there is evidence of inequitable SNAP utilization and expansion, namely reduced participation among low-income Latino households and a limited impact of SNAP expansion on minority households and those experiencing job loss [5]. While our study did not collect data on experiences with discrimination as a potential food access barrier, this is an important construct to assess in future work since racialized minorities can experience discrimination in a variety of settings, including food retail stores [51].…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity rates in the United States (U.S.) rapidly increased during the COVID-19 pandemic [1,2], with elevated rates in Black, Latino, and low-income households [3][4][5]. Food insecurity is associated with greater health care expenditures [6] and worse health behaviors and outcomes [7], including lower-quality diet [8][9][10], diet-related chronic illness (e.g., diabetes, cardiovascular disease) [7,[11][12][13][14][15], and premature death [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, sectors where participants had high percentages food insecurity also had high percentage with any income loss due to the pandemic, as seen in several other studies. 4,26,[30][31] Many occupations within these industries commonly have lower wages and minimal or no benefits such as sick leave and health care, further compounding the impact of the pandemic. A study based on the Census Household Pulse Survey found an inverse relationship between pre-pandemic income levels and financial hardship during the pandemic, which disproportionately affected Black and Hispanic Americans.…”
Section: Discussionmentioning
confidence: 99%